2015
DOI: 10.3892/mmr.2015.3705
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218, microRNA-191*, microRNA-3070a and microRNA-33 are responsive to mechanical strain exerted on osteoblastic cells

Abstract: MicroRNA (miRNA) is an important regulator of cell differentiation and function. Mechanical strain is important in the growth and differentiation of osteoblasts. Therefore, mechanresponsive miRNA may be important in the response of osteoblasts to mechanical strain. The purpose of the present study was to select and identify the mechanoresponsive miRNAs of osteoblasts. Mouse osteoblastic MC3T3-E1 cells were cultured in cell culture dishes and stimulated with a mechanical tensile strain of 2,50 με at 0.5 Hz, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Mechanical loading was reported to induce significant changes in miRNAs in pre‐osteoblastic MC3T3 cells (Guo et al, ), which suggests that miRNA might play an important role in mechanical loading mediated bone formation. Mechanical strain was shown to up‐regulate the gene expression of ALP, osteocalcin and collagen I, and enhance the activity of ALP, accompanied by the induction of miR‐218, miR‐191*, miR‐3070a, and miR‐33 expression (Guo et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical loading was reported to induce significant changes in miRNAs in pre‐osteoblastic MC3T3 cells (Guo et al, ), which suggests that miRNA might play an important role in mechanical loading mediated bone formation. Mechanical strain was shown to up‐regulate the gene expression of ALP, osteocalcin and collagen I, and enhance the activity of ALP, accompanied by the induction of miR‐218, miR‐191*, miR‐3070a, and miR‐33 expression (Guo et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
“…Mechanical loading was reported to induce significant changes in miRNAs in pre‐osteoblastic MC3T3 cells (Guo et al, ), which suggests that miRNA might play an important role in mechanical loading mediated bone formation. Mechanical strain was shown to up‐regulate the gene expression of ALP, osteocalcin and collagen I, and enhance the activity of ALP, accompanied by the induction of miR‐218, miR‐191*, miR‐3070a, and miR‐33 expression (Guo et al, ). Besides these miRNAs, the miRNA microarray also showed that the expression levels of miR‐M1‐2‐3p, miR‐let‐7e*, and miR‐3470a were much higher in the strained group than the unstrained control group while the expression levels of miR‐32, miR‐5110, and miR‐5121 were significantly lower under mechanical strain than unstrained group (Guo et al, ).…”
Section: Mechanical Stress‐mediated Bone Metabolism Through Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical strain could promote osteoblast differentiation [16,17]. In our previous study, a mechanical strain of 2500 με at 0.5 Hz for 8 hours also promoted osteoblast differentiation and four miRNAs (miR-218, 191*, 3070a and 33) were responsive to the mechanical strain [42]. However, the mechanoresponsive miRNAs of our previous study were different from the mechanoresponsive miRNAs found in this study.…”
Section: Discussionmentioning
confidence: 45%
“…Identified in several miRNA screens, miR-199a associates with osteoblast differentiation [63,64], suggesting that its identification as an ‘ostemiR’ may be linked to its control of Cox2. Additionally, while not directly linked to Cox2 , miR-218, miR-191*, miR-3010a and miR-33 were recently identified in MC3T3-E1 osteoblastic cells to be responsive to mechanical strain [65]. …”
Section: Micrornas That Control Osteoblast Identity and Homeostasismentioning
confidence: 99%